The right to freedom to choose the type of business: The case of VietNam - Lam NGUYEN VAN; Quang VU (Revista Jurídica Portucalense, 2024)
The right to freedom of business is a fundamental right enshrined in the Vietnamese constitution, the ability of subjects to do what they want, choose, and decide for themselves all matters related to business activities that are not prohibited by law. In particular, the content of the freedom to choose the type of business is considered basic and important. However, Vietnamese law only treats freedom of business as a right of enterprises and only recognizes certain types of enterprises that are considered popular, which limits citizens' freedom to choose types of businesses. This paper uses systematization, analysis, explanatory methods, and comparative jurisprudence methods, etc. to analyze theoretical issues and the current legal situation regarding the freedom to choose types of enterprises in Vietnam, propose some solutions to improve the law and effectively enforce the law, ensure the freedom to do business of citizens.